Pengaruh Kompetensi, Teknologi Informasi, Dan Komunikasi Organisasi Terhadap Kinerja Pegawai ( Studi Pada Badan Pendapatan Daerah Kota Malang ) - Abraham Affandy; Pardiman Pardiman; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine how the influence of competence, information technology and organizational communication on employee performance at the Dinas Pendapatan Daerah Kota Malang. The sample in this study were civil servants at the Dinas Pendapatan Daerah Kota Malang amounting to 66 people. This data collection method uses the method of distributing questionnaires. This data analysis technique uses multiple linear regression analysis techniques with the help of the SPSS ver 20 program. Based on the results of multiple regression analysis, it is known that competence, information and communication technology have a positive and significant effect on employee performance at the Dinas Pendapatan Daerah Kota Malang. Keywords : Competence, Information Technology, Organizational communication, employee performance